1988
DOI: 10.1042/bj2540155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface curvature on the rate of cholesterol transfer between lipid vesicles

Abstract: The effect of surface curvature on the spontaneous movement of cholesterol between membranes was investigated by measuring the rates of cholesterol transfer from donor vesicles of various sizes to a common acceptor vesicle. Donor vesicles of size in the range 40-240 nm were prepared by extruding multilamellar dispersions through polycarbonate filters of different pore sizes under pressure. The smallest donor vesicle and the acceptor vesicles were obtained by the normal sonication procedures. The rate of choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…For instance, McLean and Phillips found that the half-time for cholesterol translocation between vesicles is only 2.4 hours, 23 which is an order of magnitude less than the corresponding value for intact GPLs (see above). A similar value has been found by others, 24,25 and even faster rates (~1 hour) have been reported. 14 The rate of the spontaneous transfer of ergosterol (the cholesterol equivalent in yeast) has not been determined, but it is probably even faster than that of cholesterol due to the presence of two additional double bonds, albeit there is an extra methyl group in ergosterol.…”
Section: Factors Influencing Sltsupporting
confidence: 91%
“…For instance, McLean and Phillips found that the half-time for cholesterol translocation between vesicles is only 2.4 hours, 23 which is an order of magnitude less than the corresponding value for intact GPLs (see above). A similar value has been found by others, 24,25 and even faster rates (~1 hour) have been reported. 14 The rate of the spontaneous transfer of ergosterol (the cholesterol equivalent in yeast) has not been determined, but it is probably even faster than that of cholesterol due to the presence of two additional double bonds, albeit there is an extra methyl group in ergosterol.…”
Section: Factors Influencing Sltsupporting
confidence: 91%
“…The phospholipid bilayer of an LUV is an essentially planar surface in which the fatty acyl side chains are motionally restricted (32), compared with the curved surface of an SUV (33). It has been demonstrated that the initial insertion of the amphipathic ␣-helical regions of plasma lipoproteins into a phospholipid bilayer is facilitated by the existence of lipid packing defects caused by extreme membrane curvature or by the differential packing properties of different phospholipids within the membrane (34).…”
Section: Resultsmentioning
confidence: 99%
“…For many years, it has been known that spontaneous cholesterol exchange is faster from small sonicated bilayer vesicles than from larger, planar-like bilayers vesicles [70,[121][122]. Indeed, for the case of cholesterol and zwitterionic diacyl phopholipids [70,[121][122], it appears that the characteristics of the donor rather than the acceptor vesicles limit the transfer rate. In fact, the association rate of PC monomers with neutral acceptor vesicles has generally been thought to be diffusion limited by the aqueous mileu rather than by the interfacial characteristics of the acceptor surface [123].…”
Section: Iii-a Lamellar Physical Statementioning
confidence: 99%